Citrus sinensis and Musa acuminata Peel Waste Extract Mediated Synthesis of TiO2/rGO Nanocomposites for Photocatalytic Degradation of Methylene Blue under Visible Light Irradiation. (25th January 2022) - Olana, Mulugeta Hirko; Sabir, Fedlu Kedir; Bekele, Eneyew Tilahun; Gonfa, Bedasa Abdisa
Abstract : Water pollution caused by various natural and artificial sources such as expansion of industrialization, rapid increment in population size, the threat of climate change, and development in urbanization takes a serious attention. Due to this fact, various protocols and techniques were adopted for the treatment of such polluted water. In the present findings, TiO2 nanoparticles (NPs) and TiO2 /rGO nanocomposites (NCs) were synthesized using titanium tetra butoxide in the presence of Citrus sinensis (CS) and Musa acuminata (MA) peel waste extract as a capping, reducing, and stabilizing agent. The synthesized NPs and NCs were characterized using thermogravimetric-differential thermal analysis (TGA/DTA), X-ray diffraction (XRD), scanning electron microscope (SEM), high resolution transmission electron microscopy (HR-TEM), selected area electron diffraction (SAED) pattern, ultraviolet diffuse reflectance spectroscopy (UV-DRS), and Fourier transform infrared (FTIR) spectroscopy. The synthesized NPs and NCs were investigated as green alternative photocatalyst for the degradation of methylene blue (MB) dye under visible light irradiation. Thermal analysis results confirmed that the green synthesized TiO2 NPs were found to be too stable above 550°C. XRD analysis result showed that the average crystalline size of CS and MA mediated synthesized TiO2 NPs with various volume ratios was in the range of 7.3–27.3 nm and 13.4–22.4 nm, respectively. The average crystalline size of CS and MA peel extract template synthesized TiO2 /rGO NCs was found to be in the range of 7.5–15.3 and 11.2–12.5 nm, respectively. The band gap energy was calculated to be in the range of 3.17–3.29 eV and 3.10–3.38 eV for the CS and MA mediated synthesized TiO2 NPs, respectively. E g of CS and MA peel extract template formed TiO2 /rGO NCs was found to be in the range of 2.85–3.11 eV and 3.07–3.11 eV, respectively. SEM analysis proved that the various synthesized TiO2 NPs and TiO2 /rGO NCs were spherical in shape and the absence of any other foreign materials confirmed the purity of the corresponding nanocatalysts. In addition, TEM, HRTEM, and SAED analysis confirmed that the structures of the synthesized nanocatalysts were spherical in shape and the catalysts were too crystalline and the result was found to fit with the XRD result. Among the synthesized various volume ratios of TiO2 nanocatalysts, high percentage of degradation (62% and 58.2%) was achieved using TiO2 -2c and TiO2 -2 m, respectively. Moreover, 94.28% and 94.25% of MB degradation were achieved in the presence of TiO2 /rGO-1.5c and TiO2 /rGO-1.5c nanocomposite photocatalysts, respectively.